(untitled) (Research, Society and Development, 2020)
This research aimed to analyze the relationship between passion, resilience, and performance in triathletes. The sample was composed of 78 male athletes ( age = 36.97 ± 10.29 years), participating in two national-level competitions which took place in 2018. Instruments used were an identification sheet, the Passion Scale (PS), and the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). Athletes’ performance was obtained by their total time in the race. Data analysis was performed through R software (version 3.6.3), using the Shapiro-Wilk, Wilcoxon, Mann-Whitney’s U, Spearman correlation coefficient and Binomial Logistic Regression tests, with significance level of p<0.05. Results showed that triathletes had higher levels of harmonious (Md=5.83) rather than obsessive passion (Md=3.33) (p<0.05). Better-ranked individuals were younger (p<0.01) and more passionate about the sport (p=0.03). Harmonious passion presented a positive and moderate correlation with resilience (r=0.39). Older athletes showed smaller chances to obtain better performances (OR=0.80) whereas athletes more experienced on their sport showed greater chances (OR=1.25) (p<0.01). Obsessive passion presented a non-significant positive influence on performance (OR=1.74; p=0.07). It was concluded that athletes’ age may negatively influence performance whereas the time of practice and obsessive passion may positively influence it. Nevertheless, only harmonious passion seems to be able to aid the athlete in becoming more resilient.